Performance Monitoring Model to Increase Employee Productivity at STMIK Mardira Indonesia - Sudiryo; A Rohendi; Dasrun Hidayat (Politeknik Mardira Indonesia, 2024)
Performance monitoring is an important point for realizing the progress of a company. Effective performance monitoring is by conducting performance assessments of employees. Employee performance is always faced with the problem that employees do not have work achievement targets or Employee Work Targets (SKP). This research aims to find a performance monitoring model that can be applied at STMIK Mardira Indonesia. The research methodology used is a qualitative method with a case study approach and natural observation. The performance monitoring model that is suitable to be implemented at STMIK Mardira is a combination of Traditional Assessment, Management By Objective (MBO), 360-Degree Feedback models supported by a digital-based information system, namely the Human Resource Information System (HRIS).